The oft-overlooked cardiovascular complications of inflammatory bowel disease. (3rd April 2023) - Massironi, Sara; Mulinacci, Giacomo; Gallo, Camilla; Viganò, Chiara; Fichera, Maria; Villatore, Andrea; Peretto, Giovanni; Danese, Silvio
ABSTRACT: Introduction: Inflammatory bowel disease (IBD) may be associated with several extraintestinal comorbidities, including cardiovascular disease (CVD). Chronic inflammation is recognized as an important factor in atherogenesis, thrombosis, and myocarditis. Areas covered: IBD patients may be at increased risk for developing early atherosclerosis, cardiovascular events, peripheral artery disease, venous thromboembolism, myocarditis, and arrhythmias. Anti-tumor necrosis factor agents and thiopurines have been shown to have a protective effect against acute arterial events, but more research is needed. However, an increased risk of venous thromboembolism and major cardiovascular events has been described with the use of Janus kinase inhibitors. Expert opinion: CVD risk is slightly increased in patients with IBD, especially during flares. Thromboprophylaxis is strongly recommended in hospitalized patients with active disease as the benefit of anticoagulation outweighs the risk of bleeding. The pathogenetic relationship between CVD and IBD and the impact of IBD drugs on CVD outcomes are not fully elucidated. CVD risk doesn't have the strength to drive a specific IBD treatment. However, proper CVD risk profiling should always be done and the best strategy to manage CVD risk in IBD patients is to combine appropriate thromboprophylaxis with early and durable remission of the underlying IBD.